Investigation of piwil2 expression as a biomarker in solid tumors of childhood (Annals of Medical Research, 2021)
Aim: PIWIL 2 belongs to a subgroup of argonaute proteins, which has an essential role in germ cell development and repair. Recent studies have demonstrated PIWIL 2 as a stem cell marker in some solid tumors. In the present study, we aimed to evaluate the expression of PIWIL 2 in childhood solid tumors and to show being a potential marker for a therapeutic drug.Materials and Methods: The study included 150 patients who were diagnosed with pediatric solid tumor and followed between 2000 and 2011. Solid tumor preparations were stained with polyclonal PIWIL 2 antibody by using immunohistochemical methods.Results: Assessment of the tumor sub-groups showed that, among 30 patients with neuroblastoma, there was a strong staining in 5 (16.70%) (p=0.020). PIWIL 2 was showed strong staining in 3 (21.40%) osteosarcoma patients (p=0.030). Among 34 patients with a germ cell tumor, there was a strong staining in 6 (17.60%) patients (p=0.040).Conclusion: Significant PIWIL 2 positivity was found in neuroblastoma, osteosarcoma and germ cell tumors and it can be a potential marker for these tumors. Because of non-tumor tissue involvement in Wilms’ tumor it can be particularly useful in determining surgical margins.